Intercropping of upland rice (Oryza sativa) with maize (Zea mays) - AZIZ, M A; KHAIR, A B M ABUL; SALAHUDDIN, A B M (The Indian Journal of Agricultural Sciences, 2013)
Â A 2-year field experiment showed that intercropping of 100% rice (Oryza saliva L.) + paired row maize (Zea mays L.) gave seed yield of 0.73 + 4.16 tonnes/ha respectively. This combination gave the highestÂ· land-equivalent ratio ,of 1.39 and Rs 16 845 in gross monetary retum. It also gave the highest gross margin (Rs 11 350), rice equivalent yield (3.67) and benefit: cost ratio (2.07).